Une cave à amphores, une statue en pierre et une tête coupée de la fin de l’âge du Fer à Châteaumeillant (Cher) - Sophie Krausz; Caroline Millereux; Marion Bouchet; Fabienne Olmer (Gallia)
The oppidum of Châteaumeillant (Cher) belongs to the civitas of the Bituriges, whose boundaries correspond approximately to those of the current departments of Cher, Indre, and to which portions of Allier and Loir-et-Cher must be added. Located about 60 km from Bourges/Avaricum (Cher), the capital of this territory, the Mediolanum of the Tabula Peutingeriana occupies a privileged position at the southern end of Berry, the oppidum having been installed on the highest part of a rectangular promontory measuring 60 ha. Discovered in the 19th c. by Émile Chénon, the oppidum of Châteaumeillant was the subject of major archaeological excavations in the 1950s and 1960s under the direction of Émile Hugoniot and Jacques Gourvest. From 2001 to 2018, subsequent excavations focused on the Gallic habitat, as well as on the imposing fortification. The excavations revealed a dense and continuous occupation that began around 200 BC, through the La Tène C2 period. As early as La Tène D1, around 150 BC, shipments of Italian amphorae poured into Châteaumeillant. Then, around 100 BC, the town was equipped with a murus gallicus enclosing the 27 ha of the southern half of the promontory. The site subsequently peaked in terms of growth, though the rate of Italian wine imports remained steady. During the Gallic War, the murus gallicus was reinforced by a massive rampart preceded by a 45 m wide flat-bottomed ditch (Krausz 2007a; 2014; 2019; 2021; Krausz, Millereux 2019). Traces of fire observed in the La Tène D2 habitat suggest that Châteaumeillant is likely one of the twenty Bituriges towns to have been burnt down at the behest of Vercingetorix (Krausz 2009a). The town was rebuilt in the Augustan period and the occupation of the promontory continued through to the present day, without interruption. In the areas explored between 2008 and 2018 (A to G), several buildings, constructed on posts, were excavated. Some of them were built overtop large quadrangular pits that would have served as cellars. The archaeological material discovered in this zone argues in favour of areas B and C having served a craftworking and commercial function, rather than as exclusively residential areas. The presence of cellars and large pits, which would have been used to store foodstuffs that might be used for trading would appear to corroborate this interpretation of function. It is in this part of the oppidum that the renowned “amphorae cellars” were discovered in the 19th c. It was only possible to explore one such cellar during the recent excavations (2012 to 2016) and it is therefore the object of study of this article. The cellar contained the remains of 33 Italic amphorae. During a second phase of use, a well (St 512) was dug in the eastern half of this cellar. Its protected excavation yielded an exceptional assemblage, dated to the final La Tène period: in addition to some 1,500 ceramic sherds, an anthropomorphic stone statue, a human skull with traces of de-fleshing and an andiron protome of a horse were deposited at the bottom of the well. The body of the andiron is complete and well preserved, decorated with a combination of white paint and engravings. The object measures 0.39 m in height, from the hoof to the top of the horse’s head. An anthropomorphic statue and a human skull were discovered in the layer above. The statue was lying face down, 10 cm from the human skull. This sculpture represents a male figure, whose head and right hand were preserved; the hand is holding a ring to the centre of the chest. Below this ring, the statue was previously and intentionally broken. Following this damage, the upper portion of the statue (head and torso) was deposited in the well, while the base was found in a small pit in Zone B, located 8 m north of the well. It is sculpted in the round, in a particularly fine Châteaumeillant sandstone, finer than that of the statue from well F.II of the Kasmareck Garden discovered within the oppidum in 1960. Both are, undoubtedly, Celtic busts. In addition to this type of bust, another category of statues are seated figures, recognizable by virtue of their crossed legs (Coulon, Krausz 2013). Sitting busts present one or both hands resting on the chest and often wear a torque around the neck. In the statue’s current state, and with the upper part combined with the lower part, it measures 0.50 m in total height. Overall, the width varies little: from the head (10 cm), through the torque and the shoulders (12 cm) to the lower portion (15 cm). Thus, there is a variation of 5 cm from top to bottom, resulting in a small but constant broadening. This slight variation confirms that the statue is part of a rectangular block that widens slightly towards the bottom. Below the right hand holding the ring, the lower block presents no further figural representation. However, it has been carved in such a way as to provide an end that was likely tapered or pointed, a feature that could have allowed the sculpture to be driven into the ground. As with other Gallic bust statues, certain anatomical and ornamental features are highlighted: the facial features, the hairstyle and the ears, the torque around the neck and the representation of the right arm and hand. As for the human skull, it was deposited in the pit without its mandible or any other accompanying skeletal element. Only the molars and premolars remain from the upper dentition, while the other teeth were lost post-mortem, though not within the well. The skull belonged to a young adult, whose age was estimated between 17 and 25 years of age. The sex is undetermined, but most likely male. Several incisions visible on the calvaria (or skullcap), as well as on the zygomatic processes of the temporal bones suggest that it was de-fleshed, removing the scalp, and detaching the mandible and atlas. The polished appearance of the frontal bone, along with a small eroded area in the centre could be the result of exposure to touching or weathering, at least in this anterior portion. Similarly, the cracking and darkening of the tooth enamel could be the result of being placed in an open-air setting. The loss of the canines and incisors is further indication of the possibility that the skull was exposed, possibly showcased in an elevated manner. The Gauls’ marked interest in heads is known from ancient times, and the practice of removing skulls and subjecting them to a particular treatment, separate from the rest of the skeleton is attested to in Gaul from the 5th to the 1st c. BC. The presence of these remarkable objects in well 512 reveals the unique and ritualistic nature of the deposit, in the context of the La Tène habitat. It combines the representation of a male figure set in stone with a severed head. Well 512 and cellar 437 constitute an exceptional archaeological ensemble, unprecedented in a La Tène period habitat. Indeed, it concentrates numerous cultural and social characteristics of the La Tène D period: statuary, a ritual deposit, wells and an amphora cellar. This collaborative article proposes a detailed study of the two structures, the objects discovered therein and their chronology.